Effect of Proactive Personality on Career Decidedness: The Mediating Role of Career Exploration and the Moderating Role of Anticipated Regret - Yu, Xuan; Luo, Nan; Liu, Xuhong; Li, Haihong; Li, Ling; Mei, Yuanfei (Frontiers in Psychology, 2021)
Based on social cognitive career theory and career development theory, we explored the effect of proactive personality on career decidedness among 783 Chinese college students. A three-wave longitudinal survey showed proactive personality was positively related to career decidedness via career exploration, besides, anticipated regret moderated the relationship between proactive personality and career exploration. The theoretical significance and practical implication are discussed at the end of this research.